-2g-4+9g=4g+5

Simple and best practice solution for -2g-4+9g=4g+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2g-4+9g=4g+5 equation:


Simplifying
-2g + -4 + 9g = 4g + 5

Reorder the terms:
-4 + -2g + 9g = 4g + 5

Combine like terms: -2g + 9g = 7g
-4 + 7g = 4g + 5

Reorder the terms:
-4 + 7g = 5 + 4g

Solving
-4 + 7g = 5 + 4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-4g' to each side of the equation.
-4 + 7g + -4g = 5 + 4g + -4g

Combine like terms: 7g + -4g = 3g
-4 + 3g = 5 + 4g + -4g

Combine like terms: 4g + -4g = 0
-4 + 3g = 5 + 0
-4 + 3g = 5

Add '4' to each side of the equation.
-4 + 4 + 3g = 5 + 4

Combine like terms: -4 + 4 = 0
0 + 3g = 5 + 4
3g = 5 + 4

Combine like terms: 5 + 4 = 9
3g = 9

Divide each side by '3'.
g = 3

Simplifying
g = 3

See similar equations:

| -6(x-1)-7=7x+2 | | y=-2(y+8)-8 | | 26p=-78 | | .3n+.75=.83n-1 | | 8+3n=4/5n+15 | | 2d+15=6d+19 | | 5(n-2)-14n=-3n(5-4n) | | 4(5-8v)=-236 | | y=(y+8)(y+8) | | 7(g+12)=28 | | 4x+3-x=3 | | 7r+3=31 | | (-4+r)+6=11 | | -(-12x)-3x= | | 3x/10*6/1 | | -2+8x-6x=14 | | x-1/2=1(1/4) | | y=(y+8)(y+8)-2(y+8)-8 | | 1/2+x=2x+3/4 | | 12=-5k+32 | | (3v-1/3w)(v-1/5w) | | (X+3)/8=-6 | | 9(x-2)+6=-2 | | 2.15=x/740 | | 16x^2+150x-15=0 | | p-39=32 | | 8x-82=u | | -9-9=x | | 4+2/3x+9+1/3x | | 87=-2(-2-6x)-1 | | 16y^3-9=y-144y^2 | | X^2+2X+-4800=0 |

Equations solver categories